RT-PCR Analysis of TopBP1 Gene Expression in Hereditary Breast Cancer - Forma, Ewa; Bernaciak, Magdalena; Romanowicz-Makowska, Hanna; Bryś, Magdalena (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
Hereditary predisposition to breast cancer determined in large part by loss of function mutations in one of two genes BRCA1 and BRCA2. Besides BRCA1 and BRCA2 other genes are also likely to be involved in hereditary predisposition to breast cancer. TopBP1 protein is involved in DNA replication, DNA damage checkpoint response and transcriptional regulation. Expression of TopBP1 gene at the mRNA level was analyzed by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) in 94 samples of hereditary breast cancer. Analysis of TopBP1 mRNA level showed that expression of TopBP1 is significantly downregulated in poorly differentiated breast cancer (grade III according Bloom-Richardson system (P<0.05).